A gender perspective on counter-terrorism - Faddoul, Leila-Maria (2022)
Following the September 11 2001 attacks on the United States, terrorism has evolved to a point where it became crucial for countries to move from exclusively military counter-terrorism approaches towards rights-based and gender-inclusive ones. This study sheds light on this shift, by providing a qualitative examination of how the pertinent United Nations (UN) bodies incorporated a gender perspective into counter-terrorism strategies and adopted concrete measures in this regard. To date, 22 UN Security Council (UNSC) resolutions, as well as 7 initiatives by UN bodies, address the role of women in formulating and implementing counter-terrorism measures. These findings indicate the continuous need to keep the issue of gender at the core of all international initiatives in the domain of countering terrorism.